Do patients' symptoms and interpersonal problems improve in psychotherapeutic hospital treatment in Germany? A systematic review and meta-analysis. - Sarah Liebherz; Sven Rabung (PLoS ONE, 2014)
BACKGROUND: In Germany, inpatient psychotherapy plays a unique role in the treatment of patients with common mental disorders of higher severity. In addition to psychiatric inpatient services, psychotherapeutic hospital treatment and psychosomatic rehabilitation are offered as independent inpatient treatment options. This meta-analysis aims to provide systematic evidence for psychotherapeutic hospital treatment in Germany regarding its effects on symptomatic and interpersonal impairment. METHODOLOGY: Relevant papers were identified by electronic database search and hand search. Randomized controlled trials as well as naturalistic prospective studies (including post-therapy and follow-up assessments) evaluating psychotherapeutic hospital treatment of mentally ill adults in Germany were included. Outcomes were required to be quantified by either the Symptom-Checklist (SCL-90-R or short versions) or the Inventory of Interpersonal Problems (IIP-64 or short versions). Effect sizes (Hedges' g) were combined using random effect models. PRINCIPAL FINDINGS: Sixty-seven papers representing 59 studies fulfilled inclusion criteria. Meta-analysis yielded a medium within-group effect size for symptom change at discharge (g = 0.72; 95% CI 0.68-0.76), with a small reduction to follow-up (g = 0.61; 95% CI 0.55-0.68). Regarding interpersonal problems, a small effect size was found at discharge (g = 0.35; 95% CI 0.29-0.41), which increased to follow-up (g = 0.48; 95% CI 0.36-0.60). While higher impairment at intake was associated with a larger effect size in both measures, longer treatment duration was related to lower effect sizes in SCL GSI and to larger effect sizes in IIP Total. CONCLUSIONS: Psychotherapeutic hospital treatment may be considered an effective treatment. In accordance with Howard's phase model of psychotherapy outcome, the present study demonstrated that symptom distress changes more quickly and strongly than interpersonal problems. Preliminary analyses show impairment at intake and treatment duration to be the strongest outcome predictors. Further analyses regarding this relationship are required.